BDNF Val66Met Polymorphism Is Associated With Motor Recovery After Rehabilitation in Progressive Multiple Sclerosis Patients - Giordano, Antonino; Clarelli, Ferdinando; Cannizzaro, Miryam; Mascia, Elisabetta; Santoro, Silvia; Sorosina, Melissa; Ferrè, Laura; Leocani, Letizia; Esposito, Federica (Frontiers in Neurology, 2022)
Background: Rehabilitation is fundamental for progressive multiple sclerosis (MS), but predictive biomarkers of motor recovery are lacking, making patient selection difficult. Motor recovery depends on synaptic plasticity, in which the Brain-Derived Neurotrophic Factor (BDNF) is a key player, through its binding to the Neurotrophic-Tyrosine Kinase-2 (NTRK2) receptor. Therefore, genetic polymorphisms in the BDNF pathway may impact motor recovery. The most well-known polymorphism in BDNF gene (rs6265) causes valine to methionine substitution (Val66Met) and it influences memory and motor learning in healthy individuals and neurodegenerative diseases. To date, no studies have explored whether polymorphisms in BDNF or NTRK2 genes may impact motor recovery in MS. Objectives: To assess whether genetic variants in BDNF and NTRK2 genes affect motor recovery after rehabilitation in progressive MS. Methods: The association between motor recovery after intensive neurorehabilitation and polymorphisms in BDNF (rs6265) and NTKR2 receptor (rs2289656 and rs1212171) was assessed using Six-Minutes-Walking-Test (6MWT), 10-Metres-Test (10MT) and Nine-Hole-Peg-Test (9HPT) in 100 progressive MS patients. Results: We observed greater improvement at 6MWT after rehabilitation in carriers of the BDNF Val66Met substitution, compared to BDNF Val homozygotes (p=0.024). No significant association was found for 10MT and 9HPT. NTRK2 polymorphisms did not affect the results of motor function tests. Conclusion: BDNF Val66Met was associated with walking function improvement after rehabilitation in progressive MS patients. This result is in line with previous evidence showing a protective effect of Val66Met substitution on brain atrophy in MS. Larger studies are needed to explore its potential as a predictive biomarker of rehabilitation outcome.